From research I make art: the 4 creative feet - Damiani, Sarah Rodrigues; Sanmartin, Stela Maris (Revista do Colóquio, 2025)
This text reveals a process of artistic creation based on the investigations of the GEPCEAr/UFES research group, coordinated by Prof. Dr. Stela Maris Sanmartin. The work derives from a comparative action based on the unusual analogy method (Prado; Fernández, 2011). The writing undertaken approximates the 4 dimensions of creativity, discussed by Mel Rhodes (1961) and the essays on the imagination of matter, by Gaston Bachelard (1994-2019). It is believed that studies on creativity and the creative process are capable of reverberating poetic, artistic and creative actions. In this sense, lines of reflection are developed on the imaginative path of this production.
Keywords: art; dimensions of creativity; creative methods; poetics of the imagination; creative process